Educational Problems In The Information Society - Abdizoitovich, Ganiev (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article investigates the challenges facing modern education systems within the framework of the information society. The study aims to identify the impact of digital technologies on education and upbringing, especially regarding the spiritual and moral development of youth. Using theoretical analysis and a sociopedagogical framework, the research highlights both positive and negative influences of digitalization, including weakened student attention, family detachment, and media overexposure. Results suggest that developing digital literacy, information ethics, and spiritual resilience is essential. The paper calls for collaborative efforts among educators, families, and policymakers to shape education strategies aligned with the demands of the digital age.